SUCCESSFUL REGISTRATION OF DOMESTIC BIOANALOGUE OF BEVACIZUMAB – NEW OPPORTUNITIES FOR EFFECTIVE TREA TMENT OF PATIENTS WITH NON-SQUAMOUS CELL NON-SMALL CELL LUNG CANCER - S. V. Orlov; S. N. Fogt; M. S. Shustova (Исследования и практика в медицине)
Comparison of the efficacy and safety of drugs "Avegra®" and "Avastin®" used in combination with paclitaxel and carboplatin as first-line therapy in patients with locally inoperable or metastatic NSCLC. The study included 138 patients, male and female aged 18 to 75 years with newly diagnosed inoperable or widespread metastatic NSCLC (except squamous cell NSCLC), relevant eligibility criteria. After passing screening, patients were centrally randomized in one of the study groups in a 1:1 ratio. Treatment was carried out according to the following scheme: "Avegra®" or "Avastin®", 15 mg/kg intravenously over 90 minutes immediately after carboplatin on day 1 of each 3‑week cycle + paclitaxel 175 mg/m² intravenously over 3 hours on day 1 of each 3‑week cycle + carboplatin dose required to achieve AUC 6 mg/ml×min, intravenously over 15–30 minutes, immediately following paclitaxel, on the first day of each three-week cycle. The treatment lasted for six cycles of three weeks or until progression or until the development of intolerable toxic effects. Based on CT scan assessment performed by an independent specialist, the overall response rate (ORR, partial response rate + complete response rate) defined as a primary endpoint was 42.59% (95% CI 30.33–55.83%) in "Avegra®" arm and 39.29% (95% CI 27.58–52.27%) in "Avastin®" arm, respectively. The difference in ORR between study drug and comparator was 3.30% with 95% CI –14.96–21.40% (р =0.874, the Pearson x² test with Yates correction). The lower limit of calculated 95% CI (-14.96%) exceeds the specified non-inferiority margin and it is indicating the non-inferiority of "Avegra®" efficacy compared to "Avastin®". During the study period the incidence of adverse events, including severe adverse events (grade 3–4 according to CTCAE) related with the investigational drugs, did not have statistically significant differences in both study arms.The drug "Avegra®" in direct comparison to "Avastin®" demonstrated equal efficacy, similar safety and immunogenicity profile, equal pharmacokinetic characteristics. Based on the results of the clinical study the first biosimilar of bevacizumab — drug "Avegra®" was successfully registered in Russian Federation in November 2015 and can be recommended for use in clinical practice.